A technique for spatial resolution improvement in helium‐beam radiography. Issue 5 (10th March 2020) - Amato, C.; Martisikova, M.; Gehrke, T.
Abstract : Purpose: Ion‐beam radiography exhibits a significantly lower spatial resolution (SR) compared to x‐ray radiography. This is mostly due the multiple Coulomb scattering (MCS) that the ions undergo in the imaged object. In this work, a novel technique to improve the spatial resolution in helium‐beam radiography was developed. Increasing helium‐beam energies were exploited in order to decrease the MCS, and therefore increase the SR. Methods: The experimental investigation was carried out with a dedicated ion‐tracking imaging system fully composed of thin, pixelated silicon detectors (Timepix). Four helium beams with increasing energies (from 168.8 to 220.5 MeV/u) were used to image a homogeneous 160 mm PMMA phantom with a 2 mm air gap at middle depth. An energy degrader (ED) was placed between the rear tracking system and the energy‐deposition detector to compensate for the longer range associated with more energetic ions. The SR was measured for each beam energy. To take into account the overall impact on the image quality, the contrast‐to‐noise ratio (CNR), the single‐ion water equivalent thickness (WET) precision and the absorbed dose in the phantom were also evaluated as a function of the initial beam energy. FLUKA Monte Carlo simulations were used to support the conceptual design of the experimental setup and for dose estimation. Results: In the investigated energy interval, a total SR increase by around 30% was measured with increasing beam energy, reaching a maximum value of 0.69 lp/mm. For radiographs generated with 350 μGy of absorbed dose and 220 μm pixel size, a CNR decrease of 32% was found as the beam energy increases. For 1 mm pixel size, the CNR decreases only by 22%. The CNR of the images was always above 6. The single‐ion WET precision was found to be in a range between 1.2% and 1.5%. Conclusions: We have experimentally shown and quantified the possibility of improving SR in helium‐beam radiography by using increasing beam energies in combination with an ED. A significant SR increase was measured with an acceptable decrease of CNR. Furthermore, we have shown that an ED can be a valuable tool to exploit increasing beam energies to generate energy‐deposition radiographs.